Regulatory mechanism of interaction between Y-box-binding protein 1 and heterogenous nuclear ribonucleoprotein K in cell division cycle 25a signal pathway and lung cancer metastasis: Signal pathway and lung cancer metastasis - Fu, Lvping; Yang, Mengmeng; Ma, Yuquan (Cellular and Molecular Biology, 2023)
The research aimed to the influences of the interaction between Y-box-binding protein 1 (YBX1) and heterogeneous nuclear ribonucleoprotein K (HNRNPK) on cell division cycle protein 25 phosphatase A (CDC25a) signal pathway and the regulatory mechanism of lung cancer (LC) metastasis. A total of 34 patients diagnosed with LC pathologically were selected as the research objects, and the expression levels of YBX1, HNRNP and CDC25a in LC non-metastasis tissues and LC metastasis tissues were detected by immunohistochemistry and Western blot (WB). High-expression stable cell lines including YBX1/A549 and HNRNPK /A549 were established in the LC A549 cell strain. The expression levels of YBX1 and HNRNP in YBX1/A549 and HNRNPK /A549 were tested by RT-PCR and WB. Besides, the number of migratory cells YBX1/A549 and HNRNPK /A549 was detected by cell migration experiment, and the influences of the interaction between YBX1 and HNRNP on the expression level of CDC25a were analyzed by co-immunoprecipitation (co-IP). The results showed that the expression level of YBX1 protein in LC metastasis tissues was higher than that in LC non-metastasis tissues (P<0.001). The expression level of HNRNPK protein in LC metastasis tissues was higher than that in LC non-metastasis tissues (P<0.01). The expression level of CDC25a protein in LC metastasis tissues was higher than that in LC non-metastasis tissues (P<0.05). Compared with the Control Group of A549 cell strain and transfected blank plasmid, mRNA levels and relative protein expression levels of YBX1 and HNRNPK in YBX1/A549 and HNRNPK/A549 cell lines were both increased (P<0.001). The number of migratory cells YBX1/A549 and HNRNPK/A549 was increased compared with A549 cells and those in Control Group (P<0.001), and cell migration rate of YBX1/A549 and HNRNPK/A549 was also enhanced compared with A549 cells and those in Control Group (P<0.001). The mRNA and protein levels of YBX1 in YBX1/A549 cell line were increased compared with those in Control Group (P<0.01), and the comparison of mRNA level and protein expression level of HNRNPK in YBX1/A549 cell line with the in Control Group showed no differences (P>0.05). The mRNA level and protein expression level of HNRNPK in HNRNPK/A549 cell line were enhanced compared with those in Control Group (P<0.01), and the comparison of YBX1 level and protein expression level in HNRNPK/A549 cell line with the in Control Group demonstrated no differences (P>0.05). YBX1 antibody adopted in co-IP was coated with magnetic beads, and numerous HNRNPK protein was abundant in YBX1/HNRNPK composite. The mRNA level and protein expression level of YBX1 and HNRNPK in YBX1/A549 and HNRNPK/A549 cell lines were enhanced compared with those in Control Group (P<0.001), and the comparison of mRNA level and protein expression level of CDC25 with those in Control Group showed no differences (P>0.05). The mRNA level and protein expression level of CDC25a in YBX1/HNRNPK/A549 were both higher than those in YBX1/A549 cell line and HNRNPK/A549 (P<0.001). With being induced by YBX1 or HNRNPK, the number of migratory cells CDC25/A549 was increased compared with that in Control Group (P<0.05). The mRNA level and protein expression level of CDC25a in YBX1/HNRNPK/A549 were both significantly higher than those in YBX1/A549 cell line and HNRNPK/A549 (P<0.001). All the above results indicated that the interaction between YBX1 and HNRNP regulated the expression of CDC25a, and further got involved in LC metastasis.